Transitions between Auhcoseira and Anabaena dominance in a turbid river weir pool - Bradford S. Sherman; Ian T. Webster; Gary J. Jones; Rod L. Oliver (Limnology and Oceanography, 1998)
The transitions between the diatoms Aulacoseira spp. ( Melosira ) and the cyanobacteria Anabaena spp. as dominant phytoplankton species in a turbid‐river weir pool are shown to depend directly on the establishment or destruction of persistent thermal stratification. A transition from high to low flow through the pool resulted in the establishment of persistent thermal stratification, causing Aulacoseira to sink out of the euphotic zone at a speed of 0.95 m d −1 . Concurrently, the slightly buoyant Anabaena grew within the euphotic zone with a specific growth rate of 0.37 d −1 , climaxing after approximately 14 d at a population of 20,000–30,000 cells ml −1 , at which point its biomass may have been limited by the availability of phosphorus. The stratification thus caused the phytoplankton population to separate into two distinct layers, with Anabaena occupying the illuminated surface layer and Aulacoseira found only in the lower layer below the euphotic depth. Under stratified conditions, the ratio of the surface layer depth to euphotic depth, z sl : z eu , was approximately 1, whereas for a mixed water column that ratio was >3. Access to light appeared to be the main factor determining the dominant phytoplankton species.